ANALISIS MEKANISME SURVIVAL MASYARAKAT PRASEJAHTERA DI KAMPUNG MAWOKAUW JAYA - RULIAN TAKAYUTA; THARSISIUS PABENDON (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the Survival Mechanism of the Underprivileged Community in Mawokauw Jaya Village. The research method used is a descriptive method. In this study, the data collection techniques used are observation, questionnaires, interviews and documentation. While the data analysis instrument used is source triangulation. The results of this study indicate that the Mawokauw Jaya Village community according to 100 questionnaires to the community reached 87 families in the category of Underprivileged Families, 7 in the category of prosperous families I, 1 in the category of prosperous families II, 4 in the category of prosperous families III and 1 in the category of prosperous families III Plus. Thus, the Mawokauw Jaya village community is categorized as a pre-prosperous family community that is less able to meet daily living needs.